a, 9(x+5)2-(x-7)2
b, 49(y-4)2-9(y-2)2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
e: \(49-x^2-2xy-y^2\)
\(=49-\left(x+y\right)^2\)
\(=\left(7-x-y\right)\left(7+x+y\right)\)
d: \(16x^2-24xy+9y^2=\left(4x-3y\right)^2\)
a) \(\frac{x}{2}-\frac{11}{5}=\frac{7}{8}.\frac{64}{49}\)
\(\frac{x}{2}-\frac{11}{5}=\frac{8}{7}\)
\(\frac{x}{2}=\frac{8}{7}+\frac{11}{5}\)
\(\frac{x}{2}=\frac{117}{35}\)
\(x=\frac{117}{35}\times2\)
\(x=\frac{234}{35}\)
b) \(\frac{y}{5}+\frac{9}{2}=\frac{6}{7}.\frac{36}{49}\)
\(\frac{y}{5}+\frac{9}{2}=\frac{216}{343}\)
\(\frac{y}{5}=\frac{216}{343}-\frac{9}{2}\)
\(\frac{y}{5}=\frac{-2655}{686}\)
\(y=\frac{-2655}{686}.5\)
\(y=\frac{-13275}{686}\)
ra kết quả to quá bn ạ! Bn xem lại giúp mk nha!
a.\(9.\left(x+5\right)^2-\left(x-7\right)^2\)
\(=3^2.\left(x+5\right)^2-\left(x-7\right)^2\)
\(=\left(x+8\right)^2-\left(x-7\right)^2\)
\(=\left(x+8-x+7\right)\left(x+8+x-7\right)\)
\(=15\left(2x+1\right)\)
\(=30x+15\)
b.\(49\left(y-4\right)^2-9\left(y-2\right)^2\)
\(=7^2.\left(y-4\right)^2-3^2\left(y-2\right)^2\)
\(=\left(y+3\right)^2-\left(y+1\right)^2\)
\(=\left(y+3-y-1\right)\left(y+3+y+1\right)\)
\(=2\left(2y+4\right)\)
\(=4y+8\)
a./ \(=\left[3\left(x+5\right)\right]^2-\left(x-7\right)^2=\left(3x+15-x+7\right)\left(3x+15+x-7\right)=\left(2x+22\right)\left(4x+8\right).\)
\(=8\left(x+11\right)\left(x+2\right).\)
b./ \(=\left[7\left(y-4\right)\right]^2-\left[3\left(y-2\right)\right]^2=\left(7y-28+3y-6\right)\left(7y-28-3y+6\right)=\left(10y-34\right)\left(4y-22\right)\)
\(=4\left(5y-17\right)\left(2y-11\right)\)